The Concept of an Independent Curriculum According to Progressivism Theory - Yani, Meri; Rahmi, Intan Aulia; Paramita, Widya; Devi, Rina; Desyandri, Desyandri (International Journal of Educational Dynamics, 2023)
Education is the process of developing foundational skills that are essential for both mental and emotional intelligence. Teachers are currently facing challenges in implementing the curriculum for autonomous learning. The application of progressivism ideology to the concept of an independent learning curriculum is one possible answer to this problem. This study aims to investigate curricula for independent learning from a progressivist perspective. The library research method, which employs a philosophical hermeneutic approach and includes elements of description, interpretation, and comparison through reference studies related to the problem's theme, is the technique employed in this qualitative study in order to gain a thorough understanding of the findings. Content analysis is the method employed to examine and discover support for the notion demonstrating how the curriculum idea is separate from progressivism's philosophical tenets. A number of learning principles are extensively emphasized by progressivism, including: 1) the idea that students should be at the center of the educational process from the beginning to the conclusion; 2) Students act as engaged members of society; 3) the role of the instructor as a facilitator, offering guidance and instructions; 4) educational establishments aim to create a cooperative and democratic environment; and 5) students need to concentrate on problem solving rather than merely learning material. In opposition to progressivism's philosophical tenets, the Free Learning Curriculum aims to enhance Indonesia's human resource base, particularly during the industrial revolution 4.0.